Internet-delivered behavioral intervention to increase physical activity in persons with multiple sclerosis: Sustainability and secondary outcomes. - Dlugonski, Deirdre; Motl, Robert W.; Mohr, David C.; Sandroff, Brian M. (Psychology, Health & Medicine, 2012)
Physical activity is associated with many benefits, but persons with multiple sclerosis (MS) are less physically active than the general population. There is a critical need for research on methods of increasing and sustaining the physical activity levels of this population. This randomized controlled trial examined the efficacy of an Internet-delivered and theory-based behavioral intervention that was supplemented with video coaching for increasing and sustaining physical activity over time in persons with MS. Physically inactive, ambulatory persons with MS (N = 45) were randomly assigned to intervention (n = 22) or control (n = 23) conditions and completed a battery of questionnaires before, after, and three months after a 12-week intervention period. Data analyses were conducted in PASW 18.0. Partial eta squared ( ) effect size indicated that there was a large, statistically significant condition-by-time interaction on physical activity ( ). Cohen's d effect sizes indicated that the intervention group had a large increase in physical activity after the 12-week trial (d = .98) that was sustained over a three-month follow-up (d = .79). The current study supports the efficacy of a behavioral intervention for increasing and sustaining physical activity in a sample of persons with MS.